Analysis of ICT Literacy Skill of Fifth Grade Elementary School Students in Cirebon Border Area - Hidar Amaruddin; Nurul Iman Nurahman; Mustamid Mustamid; Sutiyono Sutiyono; Nofica Andriyati; Nur Romdlon Maslahul Adi (EduBasic Journal: Jurnal Pendidikan Dasar, 2021)
The rapid development of Information and Communication Technology (ICT) in the 21st century has influenced various aspects of people’s lives, one of which is in the educational field. ICT has a vital role in the development of learning systems. This study aims to analyze the elementary school students’ ICT literacy skills in the border area of Cirebon Regency. The research method used was a survey method with a quantitative descriptive approach. Data collection techniques utilized a questionnaire. The research sample consisted of 157 grade V elementary school students in the Sedong Sub-district located on the border of Cirebon Regency, Indonesia. The results showed that 82% of students had ICT devices, such as laptops, smartphones, or tablets, with 61% of students accustomed to using ICT devices in their daily lives for between 2-6 hours per day. However, the students’ ICT literacy level was still at level 1 out of 6 levels. Only 32% of students used ICT devices to find information as needed, and 27% of students utilized ICT devices for discussion about learning. Students used it more for entertainment, such as listening to music, watching videos, playing games, and joking with their friends on social media. In this case, students need guidance and direction in using ICT devices to be used as needed in daily life even though they are in the border area between regions. This study’s benefit is to see the percentage of elementary school students’ ICT literacy level as a preliminary study for other ongoing studies.